Injection of botulinum toxin type A (BOTOX) into trigger zone of trigeminal neuralgia as a means to control pain - Ngeow, Wei Cheong; Nair, R. (MOSBY-ELSEVIER, 360 PARK AVENUE SOUTH, NEW YORK, NY 10010-1710 USA, 2010)
This article illustrates a case of persistent trigeminal neuralgia in a medically compromised 65-year-old female who did not respond to pharmacotherapy. She had undergone several peripheral neurectomies as well as a failed right posterior fossa exploration that resulted in a cerebrospinal fluid leak. Persistent pain over the right external nasal area and right mental region was relieved for several hours after daily injections of bupivacaine. A trial of a single dose of 100 units of botulinum toxin type A (BOTOX) diluted in 2.5 mL saline was injected into the external nasal trigger zone (60 units) and to the mental nerve region (40 units). She achieved complete pain relief in the external nasal region for 5 months. Pain recurred and the site was again injected with 100 units of botulinum toxin type A (BOTOX). Pain relief at the mental region was partial. This was finally controlled with peripheral neurectomy. The patient was pain free with a maintenance dose of 200 mg carbamazepine daily for about 1 year, after which she elected to undergo stereotactic gamma knife radiosurgery when pain recurred at the external nasal region. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2010; 109: e47-e50)